Early Response to Dehydration Six-Like Transporter Family: Early Origin in Streptophytes and Evolution in Land Plants - Slawinski, Lucie; Israel, Abir; Paillot, Caroline; Thibault, Florence; Cordaux, Richard; Atanassova, Rossitza; Dédaldéchamp, Fabienne; Laloi, Maryse (Frontiers in Plant Science, 2021)
Carbon management by plants involves the activity of many sugar transporters, which play roles in sugar subcellular partitioning and reallocation at the whole organism scale. Among these transporters, the early response to dehydration six-like (ESL) monosaccharide transporters (MSTs) are still poorly characterized although they represent one of the largest sugar transporter subfamilies. In this study, we used an evolutionary genomic approach to infer the evolutionary history of this multigenic family. No ESL could be identified in the genomes of rhodophytes, chlorophytes, and the brown algae Ectocarpus siliculosus, whereas one ESL was identified in the genome of Klebsormidium nitens providing evidence for the early emergence of these transporters in Streptophytes. A phylogenetic analysis using the 519 putative ESL proteins identified in the genomes of 47 Embryophyta species and being representative of the plant kingdom has revealed that ESL protein sequences can be divided into three major groups. The first and second groups originated in the common ancestor of all spermaphytes [ζ: 340 million years ago (MYA)] and of angiosperms (ε: 170–235 MYA), respectively, and the third group originated before the divergence of rosids and asterids (γ/1R: 117 MYA). In some eudicots (Vitales, Malpighiales, Myrtales, Sapindales, Brassicales, Malvales, and Solanales), the ESL family presents remarkable expansions of gene copies associated with tandem duplications. The analysis of non-synonymous and synonymous substitutions for the dN/dS ratio of the ESL copies of the genus Arabidopsis has revealed that ESL genes are evolved under a purifying selection even though the progressive increase of dN/dS ratios in the three groups suggests subdiversification phenomena. To further explore the possible acquisition of novel functions by ESL MSTs, we identified the gene structure and promoter cis-acting elements for Arabidopsis thaliana ESL genes. The expression profiling of Arabidopsis ESL unraveled some gene copies that are almost constitutively expressed, whereas other gene copies display organ-preferential expression patterns. This study provides an evolving framework to better understand the roles of ESL transporters in plant development and response to environmental constraints.